Peracangan Interior dan Produk Portable pada Co-working Salon “Zhang Hair” di Surabaya - William William; Grace Mulyono; Poppy Firtatwentyna Nilasari (Intra, 2018)
The needs of beauty treatment in society are increasing from times. This phenomenon create higher demand for hairstyling services in big cities, for example in Surabaya. From this problem, the designer designs a co-working salon that has been equipped with a Portable box to facilitate the hairstylist while working. The portable box in Zhang hair Co-working salon provides every tool needed by the hairstylist and also can be used for outside salon services. The design method includes primary and secondary data collection. Primary data was obtained through interviews and observations. The secondary data involves literature collection that related to the design topic. The next steps in the design are data analysis, followed by the design process, and end with product realization. The design of Zhang hair co-woking salon and portable product is expected to increase hairstylists work performances.